DESA ANTIKORUPSI BERBASIS MASJID: PENINGKATAN KOMPETENSI DAI ANTIKORUPSI DEWAN MASJID INDONESIA RANTING PANGGUNGHARJO SEWON BANTUL - Suyadi, Suyadi; Suyitno, Suyitno; Akhmad, Fandi (Jurnal Abdi Insani, 2025)
Village fund corruption cases continue to rise, from 17 cases in 2016 to 155 cases in 2022. As a solution, the Corruption Eradication Commission (KPK) established anti-corruption villages, which currently number 40 across Indonesia. Panggungharjo Village, Sewon Subdistrict, Bantul Regency, is a fostered village under Ahmad Dahlan University and was the first anti-corruption village launched directly by the KPK on December 1, 2021. One important element in establishing an anti-corruption village is the presence of traditional and/or religious leaders, including the Indonesian Mosque Council (DMI). However, to date, religious leaders within DMI, particularly the Pangungharjo branch, have not contributed to the development of the Pangungharjo anti-corruption village. Therefore, the Community Service Team is here to provide a solution in the form of anti-corruption preacher training. The implementation method uses socialization, training, mentoring, program evaluation, and sustainability. The program is implemented from July to September with a duration of four meetings. Participants in the Community Service Program (PKM) were 35 members and administrators of the Panggungharjo branch of the Islamic Student Association (DMI), representing mosque administrators throughout the Panggungharjo village. The PKM results demonstrate that the anti-corruption da'i training is an innovation for Panggungharjo village, the first anti-corruption village in Indonesia. Participants experienced improvements in their knowledge of anti-corruption fiqh (Islamic jurisprudence), integrity, and anti-corruption da'wah skills. This program will continue with anti-corruption da'wah sessions at least once a month in all mosques in the Panggungharjo area.